Colombian fusel oil (2016)
By-products valorization in bio-fuels industry is an important issue for making the global process more efficient, more profitable and closer to the concept of biorefinery. Fusel oil is a by-product of bioethanol production that can be considered as an inexpensive and renewable raw material for manufacturing value-added products. In this work, results in terms of composition and physicochemical properties of six samples of fusel oil from industrial alcohol facilities are presented. Composition of the main components was established by gas chromatography. Complementary techniques, such as headspace solid-phase microextraction and gas chromatography–mass spectrometry (GC-MS), were used for detection of minor components. Fifty-five compounds were identified. Physicochemical properties such as density, acid value, moisture content and true boiling point curves were determined. Results are useful in the conceptual design of separation strategies for recovering higher alcohols, as well as to consider new options of valorization alternatives for fusel oil.